Effects of different growing media on the cut flower performances of oriental two Lilium varieties - Karagüzel, Özgül (International Journal of Agricultural and Biological Engineering, 2020)
In this study, six different growing media (peat+pumice: 1:1, v/v; peat+perlite: 1:1, v/v; rice hull+pumice: 1:2, v/v; coarse sand+peat: 2:1, v/v; soil; and cocopeat) were evaluated for their effects on the plant growth and flower quality of the oriental ‘Siberia’ and ‘Vespucci’ lily varieties. Seven hundred and twenty bulbs were planted in perforated plastic crates and placed in an unheated greenhouse. The physical and chemical properties of the growing media were examined. The number of days to flowering, plant height, the number of flowers, fresh stem weight, the number of leaves and vase life were investigated in the study. The results indicated that the use of soilless growing media significantly affected plant growth and flower quality when compared with soil. The obtained values varied by substrate type. The earliest flowering time (154.78 d) and the longest plant height (120.82 cm in the ‘Siberia’ variety) were determined in peat+pumice, whereas the largest number of flowers (7 flowers in Siberia; 5.67 flowers in Vespucci) and the highest stem weight (266.13 g in Vespucci; 353.91 g in Siberia) were recorded in cocopeat. The vase life of the plants grown in soil was longer than that of the plants grown in the soilless culture. Regarding the number of leaves, rice hull+pumice (57.42 leaves) and sand+peat (54.46 leaves) gave the best results.Keywords: Lilium varieties, growing media, plant growth, flower qualityDOI: 10.25165/j.ijabe.20201305.5173 Citation: Karagüzel Ö. Effects of different growing media on the cut flower performances of oriental two Lilium varieties. Int J Agric & Biol Eng, 2020; 13(5): 85–92.